2015
DOI: 10.3389/fcvm.2015.00020
|View full text |Cite
|
Sign up to set email alerts
|

Four Pathways Involving Innate Immunity in the Pathogenesis of Preeclampsia

Abstract: The maternal innate immune system plays an important role both in normal pregnancy as well as hypertensive disorders of pregnancy including preeclampsia (PE). We propose four pathways that involve excessive innate immunity that lead to most forms of PE. Pre-existing endothelial dysfunction plus pregnancy leads to an excessive innate immune response resulting in widespread inflammation, placental and renal dysfunction, vasoconstriction, and PE. Placental dysfunction due to shallow trophoblast invasion, inadequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 80 publications
(78 reference statements)
1
19
0
1
Order By: Relevance
“…Interestingly, our published and unpublished observations strongly suggest that dNK cells have the potential to turn into foes to pregnancy in response to inflammatory triggers. In experimental models, LPS and poly IC treatment of pregnant mice can induce alterations in the phenotype and functional characteristics of dNK cells by stimulating production of inflammatory cytokines such as TNF-α and IFN-γ [44][45][46]. In humans, it is possible that defective regulatory activation of dNK cells combined with local inflammation or intrauterine infection may program poor placentation and associated pathologies.…”
Section: Do Dnk and Peripheral Blood Nk Cells Exhibit Altered Phenotymentioning
confidence: 99%
“…Interestingly, our published and unpublished observations strongly suggest that dNK cells have the potential to turn into foes to pregnancy in response to inflammatory triggers. In experimental models, LPS and poly IC treatment of pregnant mice can induce alterations in the phenotype and functional characteristics of dNK cells by stimulating production of inflammatory cytokines such as TNF-α and IFN-γ [44][45][46]. In humans, it is possible that defective regulatory activation of dNK cells combined with local inflammation or intrauterine infection may program poor placentation and associated pathologies.…”
Section: Do Dnk and Peripheral Blood Nk Cells Exhibit Altered Phenotymentioning
confidence: 99%
“…In addition, there have been reports that women with abnormal immune responses to endogenous (autoimmunity) and exogenous (paternally derived) antigens are highly vulnerable to developing PE during the physiological stress of pregnancy [10,11]. Although all four of these scenarios originate from different initiators, they all involve the innate immune system [12].…”
Section: Introductionmentioning
confidence: 99%
“…Potential etiological factors for this complication of pregnancy include poor placentation, excessive maternal inflammation and immune response, and endothelial dysfunction . Several studies have reported that an exaggerated inflammatory response and an imbalanced immune response together play important roles in the development of pre‐eclampsia …”
Section: Introductionmentioning
confidence: 99%
“…2 Several studies have reported that an exaggerated inflammatory response and an imbalanced immune response together play important roles in the development of pre-eclampsia. [3][4][5] Among women with high-risk pregnancies, both damage- immunologic response and promote persistent inflammatory conditions by activating pattern-recognition receptors. 6 DAMPs are self-molecules primarily released as a result of non-programmed cell death in the first few hours of an injury.…”
Section: Introductionmentioning
confidence: 99%